1994
DOI: 10.1038/372475a0
|View full text |Cite
|
Sign up to set email alerts
|

Protein disaggregation mediated by heat-shock protein Hspl04

Abstract: The heat-inducible members of the Hsp100 (or Clp) family of proteins share a common function in helping organisms to survive extreme stress, but the basic mechanism through which these proteins function is not understood. Hsp104 protects cells against a variety of stresses, under many physiological conditions, and its function has been evolutionarily conserved, at least from Saccharomyces cerevisiae to Arabidopsis thaliana. Homology with the Escherichia coli ClpA protein suggests that Hsp104 may provide stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
715
0
13

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 846 publications
(743 citation statements)
references
References 21 publications
15
715
0
13
Order By: Relevance
“…The phenomenon of disaggregation was first reported in S. cerevisiae where heat denatured proteins can be efficiently reactivated by the cooperative action of Hsp70-Hsp40 and the oligomeric, ring forming AAA+ ATPase chaperone Hsp104 (Glover and Lindquist, 1998;Parsell et al, 1994). Soon after the discovery of Hsp104 disaggregase in yeast, an orthologous protein called ClpB was shown to possess disaggregation activity in E. coli and in chloroplasts and mitochondria of higher eukaryotes .…”
Section: Ii441 Chaperone Mediated Refolding and Disaggregationmentioning
confidence: 99%
“…The phenomenon of disaggregation was first reported in S. cerevisiae where heat denatured proteins can be efficiently reactivated by the cooperative action of Hsp70-Hsp40 and the oligomeric, ring forming AAA+ ATPase chaperone Hsp104 (Glover and Lindquist, 1998;Parsell et al, 1994). Soon after the discovery of Hsp104 disaggregase in yeast, an orthologous protein called ClpB was shown to possess disaggregation activity in E. coli and in chloroplasts and mitochondria of higher eukaryotes .…”
Section: Ii441 Chaperone Mediated Refolding and Disaggregationmentioning
confidence: 99%
“…For example, yeast cells expressing Hsp104p are 1000 times more viable after exposure to temperatures Ն50°C or to an ethanol concentration of 20% than cells carrying deletions of HSP104 (Sanchez and Lindquist, 1990;Sanchez et al, 1992). This survival capacity is directly attributable to Hsp104p's ability to resolubilize protein aggregates and, together with Hsp70p and Hsp40p, return them to their folded and active states (Parsell et al, 1994;Glover and Lindquist, 1998;Goloubinoff et al, 1999). This is in contrast to other heat shock proteins, which generally act by preventing aggregate accumulation or by promoting the degradation of misfolded proteins (Schirmer et al, 1996;Zolkiewski, 1999).…”
Section: Introductionmentioning
confidence: 95%
“…The same strain and plasmids used for the light/fluorescence microscopy were similarly induced before fixation for electron microscopy. The electron microscopy was carried out as described previously (Parsell et al, 1994).…”
Section: Thermotolerance and Atpase Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, hsc70 has been shown to interact with nascent proteins, and is believed to playa role in proper folding of the nascent proteins [3]. Recently, it has been shown that the yeast high molecular weight heat shock protein hsplO4 resolubilizes heat-inactivated insoluble aggregates of proteins [4]. The heat shock proteins are also involved in protein degradation.…”
Section: Introductionmentioning
confidence: 99%